Adipose specific disruption of seipin causes early-onset generalised lipodystrophy and altered fuel utilisation without severe metabolic disease - George D. Mcilroy; Karla Suchacki; Anke J. Roelofs; Wulin Yang; Yanyun Fu; Bo Bai; Robert J. Wallace; Cosimo De Bari; William P. Cawthorn; Weiping Han; Mirela Delibegović; Justin J. Rochford (Elsevier, 2018)
Objective: Mutations to the BSCL2 gene disrupt the protein seipin and cause the most severe form of congenital generalised lipodystrophy (CGL). Affected individuals exhibit a near complete loss of white adipose tissue (WAT) and suffer from metabolic disease. Seipin is critical for adipocyte development in culture and mice with germline disruption to Bscl2 recapitulate the effects of BSCL2 disruption in humans. Here we examined whether loss of Bscl2 specifically in developing adipocytes in vivo is sufficient to prevent adipose tissue development and cause all features observed with congenital BSCL2 disruption. Methods: We generated and characterised a novel mouse model of Bscl2 deficiency in developing adipocytes (Ad-B2(−/−)) using the adipose-specific Adiponectin-Cre line. Results: We demonstrate that Ad-B2(−/−) mice display early onset lipodystrophy, in common with congenital Bscl2 null mice and CGL2 patients. However, glucose intolerance, insulin resistance, and severe hepatic steatosis are not apparent. Food intake and energy expenditure are unchanged, but Ad-B2(−/−) mice exhibit significantly altered substrate utilisation. We also find differential effects of seipin loss between specific adipose depots revealing new insights regarding their varied characteristics. When fed a high-fat diet, Ad-B2(−/−) mice entirely fail to expand adipose mass but remain glucose tolerant. Conclusions: Our findings demonstrate that disruption of Bscl2 specifically in developing adipocytes is sufficient to cause the early-onset generalised lipodystrophy observed in patients with mutations in BSCL2. However, this significant reduction in adipose mass does not cause the overt metabolic dysfunction seen in Bscl2 knockout mice, even following a high-fat diet challenge. Keywords: BSCL2, Seipin, CGL2, Lipodystrophy, Adipose tissue, Browning